2021
DOI: 10.1590/0102-672020210001e1563
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Gastric Cancer Association Guidelines (Part 2): Update on Treatment

Abstract: Background : The II Brazilian Consensus on Gastric Cancer of the Brazilian Gastric Cancer Association BGCA (Part 1) was recently published. On this occasion, countless specialists working in the treatment of this disease expressed their opinion in the face of the statements presented. Aim : To present the BGCA Guidelines (Part 2) regarding indications for surgical treatment, operative techniques, extension of resection and multimodal treatment. Methods: To formulate these guidelines, the authors carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…According to GLOBACAN in 2018, gastric cancer is the fifth most common neoplasm and the third most deadly neoplasm in the world 5 . Thanks to surgical technology, oncological drugs, and medical advances in critical care units; surgical morbimortality and long-term survival have improved significantly in the past 50 years 3 , 10 , 15 , 16 . Prognostic factors of postoperative evolution are well described, and the nutritional state has proven to be a relevant short- and long-term independent factors 12 , 15 , 18 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…According to GLOBACAN in 2018, gastric cancer is the fifth most common neoplasm and the third most deadly neoplasm in the world 5 . Thanks to surgical technology, oncological drugs, and medical advances in critical care units; surgical morbimortality and long-term survival have improved significantly in the past 50 years 3 , 10 , 15 , 16 . Prognostic factors of postoperative evolution are well described, and the nutritional state has proven to be a relevant short- and long-term independent factors 12 , 15 , 18 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…GEJ tumors are very prevalent worldwide and are among the most aggressive tumors of the digestive tract 5 . Furthermore, in most western countries they are not diagnosed until the more advanced stages, when isolated surgical treatment is less effective 6 . The low rate of early gastric cancer is related to the lack of specific symptoms 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, the morbidity rate of radical gastrectomies is around 33.5% and mortality between 0.6% to 4.7% 11,16 . According to a 2015 study the overall survival of stage III/IV patients who underwent NAC and who obtained pCR was similar to those with stage I/II who did not receive NAC 6 . Recently published data demonstrated that pathological staging was better than conventional staging at predicting responsiveness to and survival after neoadjuvancy 7 .…”
Section: Introductionmentioning
confidence: 97%
“…It is estimated that more than 1 million (1,033,701) new cases of GC occurred worldwide in 2018 4 . Surgery remains the main curative treatment option, and gastrectomy with D2 lymphadenectomy is considered the standard surgical treatment for locally advanced stage 2 , 22 . Unfortunately, many patients at the time of diagnosis have already locally unresectable tumors or signs of systemic disease.…”
Section: Introductionmentioning
confidence: 99%